Upregulation of microRNA-223 expression in gingival crevicular blood of women with gestational diabetes mellitus and periodontitis - Teerat Sawangpanyangkura; Penpan Laohapand; Dittakarn Boriboonhirunsarn; Chatkoew Boriboonhirunsarn; Nattawan Bunpeng; Kallapat Tansriratanawong (Elsevier, 2022)
Background/Purpose: MicroRNA-223 (miR-223) is involved in several inflammatory diseases, including gestational diabetes mellitus (GDM) and periodontitis. We first described a procedure for purifying miR-223 from gingival crevicular blood (GCB) of pregnant women with or without GDM and periodontitis. This study aimed to determine whether GDM and/or periodontitis modifies miR-223 expression in pregnant women and to analyze miR-223-targeted messenger RNA (mRNA) expression levels in GCB compared to peripheral blood (PB). Materials and methods: Pregnant women were allocated to 4 groups: 10 women with GDM and periodontitis (GDM/P), 10 women with GDM without periodontitis (GDM/NP), 9 women with periodontitis and without GDM (NGDM/P) and 10 women without either condition (NGDM/NP). Clinical parameters of GDM and periodontal status were examined. GCB and PB were collected to assess miR-223, ICAM-1, IL-1β and β1-integrin gene expression by quantitative real-time polymerase chain reaction. Results: The GDM/P group demonstrated the highest miR-223 expression levels among the 4 groups in GCB. A significant difference was found between GDM/P and GDM/NP group (P = 0.04). In contrast, the GDM/P showed the lowest miR-223 expression level in PB among the 4 groups. Moreover, ICAM-1 and IL-1β mRNA expression exhibited the opposite trend of miRNA-223, indicating that miRNA-223 might regulate the mRNA function of those genes by epigenetic events. Conclusion: The upregulation of miR-223 expression in GCB but downregulation in PB, ICAM-1 and IL-1β genes expression in women with GDM and periodontitis suggest a promising role of miR-223 in the association between GDM and periodontitis.